The impact of demographic factors on work-family conflict and turnover intentions in the hotel industry - Tepavčević, Jelena; Vukosav, Svetlana; Bradić, Milan (Hotel and Tourism Management, 2021)
Family and work are the most important aspects in an individual’s life, and the primary goal is to find a balance between these two. Given the characteristics of working in the hotel industry, employees in this industry very often face a conflict between family and work. This study aims to measure the impact of socio-demographic characteristics (gender, age, education and marital status) on work-family conflict (WFC) and turnover intentions (TI). On the sample of 1.100 employees in different hotel facilities by applying t-test and analysis of variance ANOVA, it was found that tested socio-demographic characteristics are not significant indicators of experiencing WFC, but age and marital status are proven to be significant determinants of turnover intentions. Results obtained in this study can help managers to understand antecedents and consequences of experiencing work-family conflict and to undertake activities to reduce these conflicts and turnover intentions of employees.